Rentabilidad de las cooperativas de ahorro y crédito del segmento 1, pertenecientes al cantón Loja del último quinquenio - Cabrera Guerrero, Katherine Thalía (2024)
Credit and Savings Cooperative (CSCs) are fundamental entities of the Ecuadorian financial system, which are experiencing profitability problems, especially due to high levels of delinquency, and the quality of the loan portfolio, causing a reduction in interest income and an increase in provisions for bad loans, so it is essential to carry out an accurate quantitative analysis to identify the most important factors that influence profitability. By understanding these factors, CSCs can implement specific strategies to improve their performance. Thus, the purpose of this Curriculum Integration Paper is to analyze the profitability of segment 1 CSCs over the last five years. To achieve this, a mixed approach was used, combining the collection of qualitative information, and quantitative data through a longitudinal and non-experimental design. The population is made up of 9 cooperatives in segment 1 of the Loja canton, because these cooperatives promote local economic development. and financial inclusion. Through the financial analysis, such as the vertical and horizontal structure, significant increases were obtained in areas such as time deposits, member contributions, reserves, operating expenses and loan placement. In addition, it was found that Cooperatives JEP and CoopMego placed less than 70% of their loans, which indicates that their loan portfolio is below the ideal level. Furthermore, indicators such as ROA, ROE, liquidity, delinquency, coverage, investment, and gross portfolio were analyzed; in addition to this, two models for both ROA and ROE were made, with the result that delinquency, gross portfolio and liquidity negatively affect the performance of the CSCs. This research provided insight into the weaknesses involved in the profitability of the CSCs such as high expense levels, delinquency risks, and low loan portfolio placement.